Pyoderma gangrenosum following joint arthroplasty: a comprehensive review of clinical features, diagnosis, and management - Algarni, Abdullah (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2026)
Pyoderma gangrenosum (PG) is a rare, non-infectious neutrophilic dermatosis that may develop as a severe postoperative complication after joint arthroplasty. It often mimics surgical site infection, presenting with wound dehiscence, purulent discharge, and elevated inflammatory markers, which leads to misdiagnosis and unnecessary debridement. Surgical trauma may trigger PG through pathergy, worsening ulceration. Early recognition and prompt initiation of immunosuppressive therapy are critical to prevent morbidity, prosthesis exposure, and implant loss. This review synthesizes current evidence, emphasizing multidisciplinary management and clinical awareness to distinguish PG from infection, ensuring timely diagnosis and improved outcomes following joint replacement surgery.